Effect of a focusing electric field on the formation of arc generated carbon nanotubes - Karmakar, Soumen; Nagar, Harshada; Pasricha, R.; Seth, T.; Sathe, V. G.; Bhoraskar, S. V.; Das, A. K. (Nanotechnology, 2006)
The effect of a focusing electric field on the formation of carbon nanotubes in a direct current arc-plasma is investigated. The hard deposits on the surface of the cathode are the main products, rich in multi-walled carbon nanotubes. It is seen that the focusing electric field has a distinct influence on the yield, purity and morphology of the nanotubes. The yield of the carbon nanotubes under the `focused field condition' has been found to be higher than that derived from the normal electrode configuration. It has been observed that the deposition of carbonaceous soot on the reactor wall is considerably reduced on application of the focusing electric field. Transmission electron microscopy has been used to determine the morphology of the nanotubes. In addition, Raman spectroscopy has helped in distinguishing the graphene-like structures from the disordered carbon networks and helped in analysing the morphology of the tubes. Thermal analysis gave a qualitative estimation of the relative yield of carbon nanotubes within the cathode deposits and their thermal stabilities. The crystalline nature of the samples has been confirmed by x-ray diffraction analysis. The results clearly indicate that the focusing electric field confines the positively charged carbon precursors within the cathode-anode space causing high relative yield and purity and has a distinct effect on controlling the inner diameter of the as-synthesized carbon nanotubes.

In situ optical emission spectroscopic investigations during arc plasma synthesis of iron oxide nanoparticles by thermal plasma - Banerjee, Indrani; Joshi, N. K.; Sahasrabudhe, S. N.; Kulkarni, Naveen V.; Karmakar, Soumen; Pasricha, R.; Ghorui, S.; Tak, Atul K.; Murthy, Shri P. S. S.; Bhoraskar, S. V.; Das, A. K. (IEEE Transactions on Plasma Science, 2006)
Investigations using in situ precursor spectroscopy during the growth of nanoparticles of iron oxide by thermal plasma induced gas phase condensation method have been shown to be useful for correlating the size of nanoparticles with existing plasma parameters. The relative abundance of ionized Fe species inside the plasma plume is seen to directly establish the relation between particle size, arc current, arc length, and ambient pressure of the reacting oxygen gas. The argon plasma from a transferred arc reactor is made to impinge on the anode that is allowed to vaporize and react with oxygen. The spectral line profiles of both Ar and Fe along the plasma column during the synthesis of nanoparticles have been proved to be useful in understanding the growth mechanism. Band intensities of FeO molecular states indicated the inverse relation with particle sizes that have been correlated to the two competitive processes in which energy is released, namely: 1) one involving the radiative transition and 2) the other that of the growth by coagulation. Atomic Boltzmann plots are used for estimating the temperatures of the zones, whereas particle sizes have been inferred using transmission electron microscopic measurements.
Keywords: plasma arc device; plasma-materials processing applications; spectroscopy

Preparation of gamma-Fe2O3 nanoparticles using DC thermal arc-plasma route, their characterization and magnetic properties - Banerjee, Indrani; Khollam, Y. B.; Balasubramanian, C.; Pasricha, R.; Bakare, P. P.; Patil, K. R.; Das, A. K.; Bhoraskar, S. V. (Scripta Materialia, 2006)
gamma-Fe2O3 particles were prepared, for the first time, using a direct current thermal arc-plasma route. The powder was characterized using X-ray diffraction, Mossbauer spectroscopy, X-ray photoelectron spectroscopy, chemical analysis, vibrating sample magnetometry C and transmission electron microscopy. The high purity, stoichiometry and spherical morphology of the gamma-Fe2O3 particles (saturation magnetization = 79 emu g(-1) and coercivity = 348 Oe) were confirmed. (c) 2006 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: chemical analysis; DC thermal arc-plasma route; maghemite; Mossbauer spectroscopy; XPS

Mossbauer spectroscopic investigations of nanophase iron oxides synthesized by thermal plasma route - Nagar, Harshada; Kulkarni, Naveen V.; Karmakar, Soumen; Sahoo, B.; Banerjee, Indrani; Chaudhari, P. S.; Pasricha, R.; Das, A. K.; Bhoraskar, S. V.; Date, Sadgopal K.; Keune, W. (Materials Characterization, 2008)
Magnetic nanoparticles of iron oxide were synthesized by transferred arc plasma induced gas phase condensation method. Structural, morphological and magnetic studies of the as synthesized powder were carried out using X-ray diffraction, transmission electron microscopy and Mossbauer spectroscopy. These studies have revealed the simultaneous nucleation and condensation of different magnetic phases with a broad size distribution of the nanoparticles which is peaked at 30-50 nm and ranges from 10 nm to 80 nm. 57 Fe Mossbauer spectra recorded at various temperatures (5 K-300 K) in presence of external magnetic field (at 5 K) have suggested the presence of different phases of iron oxide with sizable amounts of gamma-Fe2O3 and alpha-Fe2O3 in addition to Fe3O4. The relative concentrations of these phases have been obtained by a self consistent spectral area analysis and were found to be 44:22:34 (%). (C) 2007 Elsevier Inc. All rights reserved.
Keywords: iron oxides; Mossbauer spectroscopy; phase analysis; plasma synthesis

Effect of leakage current and dielectric constant on single and double layer oxides in MOS structure - Laha, Pinaki; Panda, A. B.; Dahiwale, S.; Date, Kalyani S.; Patil, K. R.; Barhai, P. K.; Das, A. K.; Banerjee, Indrani; Mahapatra, S. K. (Thin Solid Films, 2010)
MOS structure of Al/Al2O3/n-Si, Al/TiO2/n-Si and Al/Al2O3/TiO2/n-Si was obtained by deposition of Al2O3 and TiO2 on silicon substrate by RF Magnetron Sputtering system. The total thickness of the oxide layer similar to 40 +/- 5 nm in the MOS structure was kept constant. Samples were characterized by X-Ray diffraction (XRD). X-Ray photoelectron spectroscopy (XPS), Impedance analyzer and Current-voltage (J-V) characteristics. The variations in the dielectric constant and tan 8 of the MOS capacitor in the frequency range of 1000Hz-1MHz were measured by impedance analyzer. The variation in dielectric constant of the Al/Al2O3/TiO2/n-Si multilayer compared to single layer of Al/Al2O3/n-Si and Al/TiO2/n-Si is due to high probability of defects, lattice mismatch and interface interactions. The steep rise of Tan 6 values in the Al/Al2O3/TiO2/n-Si structure is due to the resonance effect of both Al2O3 and TiO2 layers. The leakage current mechanisms of MOS structures were extracted from Schottky coefficient and Poole-Frenkel coefficient. Theoretical values of Schottky coefficients (beta(SC)) and Poole-Frenkel coefficients (beta(PF)) for each sample were estimated using the real part of the dielectric constant. The experimental values were calculated from J-V characteristics and compared with theoretical values. The appropriate model has been proposed. It was found that Schottky and Poole-Frenkel mechanisms are applicable at low and high field respectively for all MOS structures. The combination of Al/Al2O3/TiO2/n-Si is found to be a promising structure with high dielectric constant and low leakage current suitable for MOS devices. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Al2O3; dielectric constant; Leakage current; MOS device; Poole-Frenkel emission; Schottky emission; TiO2

Study of the effect of plasma-striking atmosphere on Fe-oxidation in thermal dc arc-plasma processing - Banerjee, Indrani; Khollam, Y. B.; Mahapatra, S. K.; Das, A. K.; Bhoraskar, S. V. (Journal of Vacuum Science & Technology A, 2010)
The effect of plasma-striking atmosphere: air and air+Ar-gas on the crystallization of Fe-oxide phases was studied using dc thermal arc-plasma processing route. The powders were characterized by x-ray diffraction, vibrating sample magnetometry, transmission electron microscopy, and Mossbauer spectroscopy techniques. At room temperature and O(2) rich atmosphere, arc-evaporated Fe(2+) ions oxidize into either gamma-Fe(2)O(3) or Fe(3)O(4) depending upon the combining ratio of Fe with molecular O(2). Fe/O ratio could be adjusted using proper flow rate of Ar gas to crystallize the pure gamma-Fe(2)O(3). (C) 2010 American Vacuum Society. [DOI: 10.1116/1.3504597]

Magnetic properties of thermal plasma synthesized nanocrystalline nickel ferrite (NiFe2O4) - Nawale, Ashok B.; Kanhe, Nilesh S.; Patil, K. R.; Bhoraskar, S. V.; Mathe, Vikas L.; Das, A. K. (Journal of Alloys and Compounds, 2011)
A rapid synthesis method is reported for magnetic nanoparticles of nickel ferrite involving thermal plasma assisted vapor phase condensation process. The as-synthesized samples were characterized by X-ray Diffraction, Transmission Electron Microscopy, Vibrating Sample Magnetometer and X-ray Photoelectron Spectroscopy techniques. The average particle size was determined from the TEM micrographs and found to be around 30 nm. The effects of reactor parameters on the magnetic and structural properties have been evaluated, to find the optimized parameters so as to achieve the highest values of saturation magnetization and coercivity. Reasonably high saturation magnetization (48 emu/g) has been assigned to the high degree of crystallinity, achieved on account of high temperature during the growth, and the cation redistribution. The high value of coercivity (1150e) is explained on the basis of possible lattice defects arising from the cation redistribution. Detailed analysis of cation distribution using the XRD line intensity data leads to the conclusion that these samples are iron deficit and nickel rich. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: crystal structure; Magnetic measurements; Magnetization; Nanostructured materials; TEM

Magnetic properties of nanocrystalline CoFe2O4 synthesized by thermal plasma in large scale - Nawale, A. B.; Kanhe, Nilesh S.; Patil, K. R.; Reddy, V. R.; Gupta, A.; Kale, B. B.; Bhoraskar, S. V.; Mathe, Vikas L.; Das, A. K. (Materials Chemistry and Physics, 2012)
The paper reports the large scale synthesis of nanoparticles of CoFe2O4 using thermal plasma reactor by gas phase condensation method. The yield of formation was found to be around 15 g h(-1). The magnetic properties of CoFe2O4, synthesized at different reactor powers, were investigated in view of studying the effect of operating parameters of plasma reactor on the structural reorganization leading to the different cation distribution. The values of saturation magnetization, coercivity and remanent magnetization were found to be influenced by input power in thermal plasma. Although the increase in saturation magnetization was marginal (61 emu g(-1) to 70 emu g(-1)) with increasing plasma power; a significant increase in the coercivity (552 Oe to 849 Oe) and remanent magnetization (16 emu g(-1) to 26 emu g(-1)) were also noticed. The Mossbauer spectra showed mixed spinel structure and canted spin order for the as synthesized nanoparticles. The detailed analysis of cation distribution using the Mossbauer spectroscopy and X-ray photoelectron spectroscopy leads to the conclusion that the sample synthesized at an optimized power shows the different site selective states. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic materials; magnetic properties; Mossbauer spectroscopy; Nanostructures